Țibbun Nabawī as a Drug Recovery Strategy: Rebuilding Norms and Self-Identity - Wulan Ayu Indriyani; Oong Komar; Yanti Shantini; Sri Maslihah (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
Recovery from drug addiction is a complex process that requires a holistic approach that encompasses physical, mental, social and spiritual aspects. This research explores Țibbun Nabawī, a prophetic medicine approach derived from the teachings and practices of the Prophet Muhammad, as an effective rehabilitation strategy for victims of drug abuse at at Yayasan Pengasih Insan Karima (YAPIKA), Indonesia. Unlike conventional rehabilitation methods, Țibbun Nabawī integrates spiritual healing with physical and psychological recovery, which plays an important role in rebuilding social norms and personal identity. This research used a qualitative approach with a case study method. Data collection methods include in-depth interviews, observation, and document analysis. The analytical technique utilized is the source triangulation analysis method, which incorporates principles from spiritual-based recovery and social identity theory. The research findings reveal that the integration of Islamic values in rehabilitation strengthens individuals' motivation to overcome addiction. Spiritual practices such as Qur'an memorization, ażān therapy, and Islamic studies significantly enhance spiritual awareness, while group therapy and social skills training help rebuild social relationships. This study contributes to the discourse of faith-based rehabilitation by mapping Țibbun Nabawī as a structured and holistic addiction recovery strategy. The findings offer practical recommendations for policy makers, rehabilitation centers, and communities to implement a more effective and sustainable recovery framework. Ultimately, this study highlights the importance of integrating Islamic teachings in social rehabilitation, which paves the way for further research on the effectiveness of faith-based approaches in treating addiction.